ANALISIS PENERAPAN MANAJEMEN RISIKO KEBAKARAN PADA GUDANG CAT DI PT. X KOTA BATAM TAHUN 2018 - ANDI SARBIAH; krismadies; M. Kafit; Dian Rizki Safarindah (Jurnal Kesehatan Ibnu Sina (j-kis), 2022)
Fire is a fire that is uncontrolled, unwanted or beyond ability and allows humans who can issue material, mental, or environmental money. Fires are very likely to occur in cat warehouses. At PT. X there was 1 case of fire in 2010. The purpose of this study was to study management at the warehouse at PT. X Batam City in 2018. This study uses a method. Direct and interviews based on checklists and interview guidelines. Data analysis is used with source (data) triangulation approach and triangulation method to test data eternity. The informants in this study were managers, financial staff, admin staff and warehouse heads. It’s known that the implementation of management at PT.X Batam City has not been carried out properly, because it has not implemented the aspects: vision-mission, human resources, regulations, facilities and infrastructure, identification and handling, control and communication and consultation. Suggestions for PT.X are to make company commitments or K3 policies, carry out control activities and responsibilities for employees.